Exponential polystability of separable motions - Martynyuk, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We establish conditions of exponentialx 1-stability and polystability for systems with separable motions. Stability conditions of these types are obtained by using the Lyapunov functions (scalar and matrix).